2021
DOI: 10.1186/s13031-021-00347-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health at conflict borders: a cross-sectional survey of human rights violations and perinatal outcomes at the Thai-Myanmar border

Abstract: Background Human rights violations (HRVs) are common in conflict and displacement contexts. Women are especially vulnerable to HRVs in these contexts, and perinatal health is acutely sensitive to related stressors and health care barriers. However, how HRVs affect immediate and long-term perinatal health in chronic displacement settings has not been closely investigated. Furthermore, it remains unclear whether and how HRVs in these contexts are tied directly to displacement circumstances or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Our study found that access to and utilization of basic health services including services for ANC, safe delivery, access to drugs and medication, neonatal and child health care were key challenges for the FDMNs living in Bangladesh. Previous studies conducted among the refugees Rawal et al glob health res policy (2021) 6:39 and migrants in Thailand [31] and countries of Southeast Asia [32] also highlighted similar problems. A study by Koning and colleagues reported that the Myanmar refugee mothers living in Thai-Myanmar border who experienced human right violations had significantly higher odds of unmet ANC need, suffered birth complications, low-birth of new-born babies and poor maternal and child health compared to those who did not experience human right violation [31].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our study found that access to and utilization of basic health services including services for ANC, safe delivery, access to drugs and medication, neonatal and child health care were key challenges for the FDMNs living in Bangladesh. Previous studies conducted among the refugees Rawal et al glob health res policy (2021) 6:39 and migrants in Thailand [31] and countries of Southeast Asia [32] also highlighted similar problems. A study by Koning and colleagues reported that the Myanmar refugee mothers living in Thai-Myanmar border who experienced human right violations had significantly higher odds of unmet ANC need, suffered birth complications, low-birth of new-born babies and poor maternal and child health compared to those who did not experience human right violation [31].…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies conducted among the refugees Rawal et al glob health res policy (2021) 6:39 and migrants in Thailand [31] and countries of Southeast Asia [32] also highlighted similar problems. A study by Koning and colleagues reported that the Myanmar refugee mothers living in Thai-Myanmar border who experienced human right violations had significantly higher odds of unmet ANC need, suffered birth complications, low-birth of new-born babies and poor maternal and child health compared to those who did not experience human right violation [31]. Similarly, the WHO Southeast Asia Regional Office (SEARO) (2018) reported that the refugees and migrants in the region suffer a range of reproductive and maternal health related problems [32].…”
Section: Discussionmentioning
confidence: 66%
“…The extent to which intensive panel data collection can work among other populations originating from and residing in different locations therefore remains an open question. Nonetheless, a growing body of qualitative research and cross-sectional data on MNP across Latin America and in Europe, Jordan, southeast Asia, and sub-Saharan Africa provides new, contextually specific insights about the opportunities and needs for intensive panel data collection with MNP originating from and living in distinct political and cultural settings [ 27 , 70 72 ]. Third, in order to participate in our panel survey, participants needed to access a cellphone and the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Food shortages and forced labor have been reported 11. Displacement resulting in resource and property deprivation has increased pregnancy complications in Karen state, with 16% of women having preterm births 12…”
Section: Goals and Challengesmentioning
confidence: 99%